2011
DOI: 10.1007/s00296-011-2301-4
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of early mortality in systemic sclerosis: a case–control study comparing early versus late mortality in systemic sclerosis

Abstract: To compare the characteristics of patients with systemic sclerosis who died within 2 years of diagnosis to those who died after 2 years of diagnosis. A retrospective chart review of all medical records of deceased systemic sclerosis (SSc) patients who had been followed at our institution from 1985 to 2007 was performed. We identified 87 deceased SSc patients within this period. From the 87 deceased individuals, 20 had died within 2 years after they were diagnosed, and 67 had died after 2 years of their diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The mRSS is a semi- quantitative scale based solely on the examiner’s subjective assessment of the severity/degree of skin induration at 17 pre-specified sites ranging from 0 to 3 at each site, thus providing a total score range from 0 to 51, depending of the degree of perceived skin thickening [85,86]. Whereas there is no consensus about the cut point for defining rapid progression in either skin or internal organ involvement, numerous studies have demonstrated that patients with rapidly increasing mRSS have substantially higher mortality than patients with slow progression [87,88]. In addition, older age at presentation, presence of tendon friction rubs and elevated erythrocyte sedimentation rates are factors related with worse clinical prognosis.…”
Section: Clinical Presentation and Clinical Subsets Of Sscmentioning
confidence: 99%
See 1 more Smart Citation
“…The mRSS is a semi- quantitative scale based solely on the examiner’s subjective assessment of the severity/degree of skin induration at 17 pre-specified sites ranging from 0 to 3 at each site, thus providing a total score range from 0 to 51, depending of the degree of perceived skin thickening [85,86]. Whereas there is no consensus about the cut point for defining rapid progression in either skin or internal organ involvement, numerous studies have demonstrated that patients with rapidly increasing mRSS have substantially higher mortality than patients with slow progression [87,88]. In addition, older age at presentation, presence of tendon friction rubs and elevated erythrocyte sedimentation rates are factors related with worse clinical prognosis.…”
Section: Clinical Presentation and Clinical Subsets Of Sscmentioning
confidence: 99%
“…Based on the assessment of the clinical course of a large number of SSc patients followed at the Scleroderma Center of our Institution [81,87,89,90], and considering that SSc-associated ILD is not reversible but can only be stabilized with arrest in its progressive course, we have used of the following criteria for defining patients with rapidly progressive SSc:…”
Section: Clinical Presentation and Clinical Subsets Of Sscmentioning
confidence: 99%
“…Factors previously associated with increased mortality have included male sex, older age at disease onset, dcSSc subtype, and the presence of serum antitopoisomerase I antibodies (ATA) as well as cardiovascular, pulmonary, and renal disease involvement 14,24,26,27,28,29,30,31,32,33,34,35 .…”
mentioning
confidence: 99%